2022
DOI: 10.3389/fpsyg.2022.1003587
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among nursing students’ self-concept clarity, meaning in life, emotion regulation ability and depression: Testing a moderated mediation model

Abstract: ObjectiveSelf-concept clarity as an inducing factor of depressive symptoms has been confirmed in previous studies. However, little is known about how and when it induces depressive symptoms in nursing students. The study is to examine the potential mediating role of meaning in life and the moderation of emotion regulation ability in the association between self-concept clarity and depressive symptoms among college nursing students.Materials and MethodsA sample of 488 college nursing students participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Previous empirical studies have also demonstrated a significant negative association between self-concept clarity and depression and social anxiety. Additionally, research has shown that college students with lower self-concept clarity scores are more likely to experience higher levels of depression and social anxiety [ 30 , 44 ]. Self-concept clarity has been found to have a positive correlation with the sense of meaning in life and subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Previous empirical studies have also demonstrated a significant negative association between self-concept clarity and depression and social anxiety. Additionally, research has shown that college students with lower self-concept clarity scores are more likely to experience higher levels of depression and social anxiety [ 30 , 44 ]. Self-concept clarity has been found to have a positive correlation with the sense of meaning in life and subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, college students with high levels of presence of meaning in their lives have psychological resources for coping with depression. However, those with low presence of meaning often experience depression in the context of meaninglessness (Hong et al, 2022). Overall, this study confirmed that future self‐continuity can indirectly influence depression by affecting the presence of meaning.…”
Section: Discussionmentioning
confidence: 99%
“…This association likely arises from clearer goal setting and reduced stress/depression (Coutts et al, 2023), even promoting healthier gaming habits (Green et al, 2021). The positive link between self-concept clarity and meaning in life has been reported among Turkish university students (Çebi & Demir, 2022) and Chinese nursing students (Hong et al, 2022). In one cross-cultural study, self-concept clarity had no significant link to the psychological outcome in a collectivistic culture, but a significant correlation was observed in an individualistic culture (Quinones & Kakabadse, 2015).…”
Section: Introductionmentioning
confidence: 97%